Effectiveness of Midwife-led Structured Education Intervention on Optimal Breastfeeding Knowledge Among Primigravid Women in Nigeria: A Randomised Control Trial (African Journal of Biomedical Research, 2024)
Breastmilk is a priceless essential food for the first six months of life and yet sub-Saharan Africa has neonatal deaths attributed to sub optimal breastfeeding. The study assessed the effectiveness of lecture and lecture with demonstration in optimal breastfeeding knowledge among women. The study adopted a quasi-experimental randomized design. A sample of 141 was determined from a population of 191 primigravid women attending antenatal clinics in General Hospitals Enugu Nigeria. A researcher developed validated was used to collect data from 63 intervention and 76 control group. A pretest was conducted and intervention was given to the participants while posttests were conducted at different times after intervention. Data were analyzed using SPSS version 26.0. Descriptive statistics was used to present sociodemographic variables and objectives of the study while inferential statistics were used to ascertain the effectiveness of the intervention. at 0.05 level of significance.  Results showed that most of the participants were in the age range of 21-30 years. The Pre-intervention knowledge level was poor in both groups and after intervention knowledge levels increased over time higher in the intervention than in the control group. Hypotheses tested revealed that educational interventions were effective as those in the intervention groups were significantly more knowledgeable than those in the control group. Antenatal care attendance was a significant predictor of knowledge of optimal breastfeeding.  The researcher concluded that lectures with demonstration during antenatal are effective in improving knowledge level of optimal breastfeeding and recommended that authorities implement policy instituting breastfeeding support groups in hospitals.